Negosiasi toleransi di ruang digital: Praktik pluralisme generasi z Indonesia dalam interaksi media sosial - Khamidah, Lailatul LailatulKhamidah (Maliki Interdisciplinary Journal, 2026)
Changes in digital technology have influenced how Generation Z in Indonesia understands and embodies the value of tolerance in their daily lives. Social media is now not only a place for self-expression but also a space for interaction where the process of negotiating pluralistic values takes place openly and continuously. This article aims to examine how Generation Z builds, maintains, and discusses attitudes of tolerance in their digital interactions, as well as to identify the various factors that influence their approach. This research uses a qualitative approach with a literature review method, namely by reading and analyzing various academic sources, such as scientific journals and books related to the issues of tolerance and pluralism in the digital space. The results show that Generation Z prefers an inclusive attitude and values equality in online interactions. However, this practice still faces various challenges, such as sharp differences of opinion, the emergence of hate speech, and the impact of bias in algorithms. In this context, tolerance is fluid and the conversation continues to evolve according to the situation and the nature of the audience. Therefore, improving critical thinking skills in using technology and understanding ethical values in communication are crucial to fostering a better and more developed pluralistic attitude in online interactions.